2021
DOI: 10.1007/s40615-020-00950-0
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in Burnout: a Systematic Review

Abstract: Background Awareness of burnout and its implications within the medical field has been growing. However, an understanding of the prevalence and consequences of burnout among underrepresented minority (URM), specifically underrepresented minority in medicine (UiM) populations, is not readily available. Objective To examine literature investigating burnout among UiM compared to non-UiM, with particular attention to which measures of burnout are currently being used for which racial/ethnic groups. Methods The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 62 publications
2
28
2
1
Order By: Relevance
“…While causes for lower burnout in Black and Latinx workers in our study are not clear, a recent systematic review suggests that inconsistent burnout findings in underrepresented groups in medicine (UiM) may be due to the failed accounting of structural and systemic barriers that inform UiM's lived experiences including racism, tokenism, and lack of inclusion or social support [36]. High rates of burnout (61.8%) among the large number (2,667) in the "prefer not to indicate" race/ethnicity category may, in part, explain these racial and ethnic differences in burnout, particularly if most of those in this category were minoritized individuals.…”
Section: Discussionmentioning
confidence: 57%
“…While causes for lower burnout in Black and Latinx workers in our study are not clear, a recent systematic review suggests that inconsistent burnout findings in underrepresented groups in medicine (UiM) may be due to the failed accounting of structural and systemic barriers that inform UiM's lived experiences including racism, tokenism, and lack of inclusion or social support [36]. High rates of burnout (61.8%) among the large number (2,667) in the "prefer not to indicate" race/ethnicity category may, in part, explain these racial and ethnic differences in burnout, particularly if most of those in this category were minoritized individuals.…”
Section: Discussionmentioning
confidence: 57%
“…Previous research has reported that these variables can influence burnout. 6,25,26 Practice variables, collected as part of the larger IBH-PC study, included setting (academic, hospital, community health center, private), nonprofit status, specialty (family medicine, internal medicine, mixed), provider full-time equivalents, tenure of behavioral health services, degree of behavioral health integration, training of medical residents, panel size, number of patient encounters, and proportion of Medicare patients. Publicly available county-level variables were matched on the location of the practice.…”
Section: Methodsmentioning
confidence: 99%
“…11,19 However, the degree to which these experience contribute to burnout among medical students who are URIM is not known. 6,20 This study assessed how the medical school learning environment (ie, the social, mental, and physical space for medical students) contributes to burnout among medical students who are URIM. 21 Previous work has demonstrated that a poor medical school learning environment can lead to medical student burnout.…”
Section: Introductionmentioning
confidence: 99%